ANALISIS PENENTUAN HARGA PENAWARAN UMUM PERDANA SAHAM (IPO) DI BURSA EFEK INDONESIA DENGAN MENGGUNAKAN METODE REAL OPTION (Studi Kasus Perusahaan yang melakukan IPO di Bursa Efek Indonesia) - Deni Pandu Nugraha (SEGMEN Jurnal Manajemen dan Bisnis, 2014)
This research applies the Real Option model based on the Black and Scholes equation and simultaneously used the implied volatility model to calculate the price of the variant. The result is deviation of the Real Option Model to actual price less than the discounted cash flow model, which shows that the Real Option Model is more accurate than discounted cashflow model. This research also developed an equation to predict the shares price after IPO, whether it will go the state of being undervalued or overvalued. The logistics equation with the independent variable is equal to the option variable from the Black and Scholes equation.   Keywords : Logistic Equation, Real Option, Overvalue, Undervalue